2020
DOI: 10.21203/rs.3.rs-29543/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence of osteoradionecrosis of the jaws: A retrospective study of 620 head and neck cancer patients treated by radiotherapy

Abstract: Background This study aims to assess systemic and local risk factors influencing the development of osteoradionecrosis of the jaws (ORN) and its incidence in head and neck cancer patients undergoing radiotherapy.Methods This was a retrospective cohort study of 620 adult patients following radiation for a head and neck cancer in 2011 or 2012. Results Of the 181 patients who did not require any extraction, the incidence of ORN was 0.5%. Of the 266 patients with 1491 dental extractions (mean 5.5 teeth per patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 37 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Kabir et al stated during RT is the worst time for extractions and best time for post-RT extractions is between 6 weeks and 4 months after RT [11]. However, Liao et al reported that tooth extraction during RT did not significantly increase risk of ORN (HR = 1.303, P = 0.4862) and post-RT extraction after 6 months of RT increase risk of ORN.…”
Section: Extractions Post Radiation Therapymentioning
confidence: 99%
See 4 more Smart Citations
“…Kabir et al stated during RT is the worst time for extractions and best time for post-RT extractions is between 6 weeks and 4 months after RT [11]. However, Liao et al reported that tooth extraction during RT did not significantly increase risk of ORN (HR = 1.303, P = 0.4862) and post-RT extraction after 6 months of RT increase risk of ORN.…”
Section: Extractions Post Radiation Therapymentioning
confidence: 99%
“…ORN can develop from months to years after RT [3] with Sapienza et al [14] reporting that ORN can develop even 5-10 years post-RT. Multiple studies reported post-RT incidence of ORN was higher in males than females [3,5,11,13,15] because incidence of HNC is higher in males and behavioural factors linked to ORN development and HNC risk being more common in males [16,17].…”
Section: Incidence Of Osteoradionecrosismentioning
confidence: 99%
See 3 more Smart Citations